Effectiveness of the four- factor Model of Mindfulness and Self-Compassion training on Life satisfaction and Resilience of Elderly Women - Asadi Bijaeyeh, Jahan Sadat; AmiriMajd, Mojtaba; Ghamari, Mohammad; Fathi Aghdam, Ghorban (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The purpose of the study was survey of Effectiveness of the Four -Factor Model of Mindfulness and Self-Compassion training on Life Satisfaction and Resilience of Elderly Women. Methods: method was semi-experimental with pre-test, post-test design with control and follow-up groups. The statistical population consisted of 473 elderly women who were residents in Guilan province in nursing homes in 2020. A sample of 45 individuals were selected by purposeful sampling method according to inclusion and exclusion creteria and were randomly divided into three groups, respectively Mindfulness Experimental Group (15 participants), Self-Compassion (15 participants) and Control Group (15 participants). For first experimental group, 8 sessions of Kabat – zinn’s (1991) mindfulness training and for the other experimental group, 8 sessions of Gilbert’s (2015) self-compassion training were performed (one session in a week and 2 Hours per-session). There was no intervention in the control group. Participants were evaluated in three groups at pre-test, post-test and follow-up stages using Diner et al’s Life Satisfaction Questionnaire. And Conner & David Son’s Resilience Questionnaire. repeated measures analysis of variance was used to analyze the data. Results: The results showed that the 4-factor model of mindfulness and self-compassion improved the life satisfaction and resilience of older women in the post-test (p <0.05), and this effect was permanent in the follow-up phase (p <0.05). Conclusion: Therefore, this intervention can be used effectively as part of therapeutic interventions in nursing homes.